2003
DOI: 10.1159/000070025
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Effects of Allogeneic versus Autologous Blood Transfusion in Patients Undergoing Radical Oesophagectomy

Abstract: Blood transfusion is often required in patients undergoing radical oesophagectomy, and is associated with immunosuppression that may worsen postoperative and long-term outcomes. However, the immunologic effects of allogeneic versus autologous transfusion have not been studied in this group of patients. We analyzed 103 patients who underwent radical oesophagectomy for oesophageal cancer, including 45 patients who received allogeneic transfusions (Allo), 16 patients who donated autologous blood but were not tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…However, patients who required blood transfusion may have a short period of local hypoperfusion in some organs such as liver and lung, potentially enhancing the recurrence or metastatic process via depression of the immune system. Several reports have suggested that blood transfusion is a significant prognostic factor of outcomes in patients who underwent surgical resection of cancer [15,16,30,31]. The mechanisms involved in the adverse effects of red blood cell transfusion may be related to impaired immunity or enhanced inflammation, which may lead to tumor growth or recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients who required blood transfusion may have a short period of local hypoperfusion in some organs such as liver and lung, potentially enhancing the recurrence or metastatic process via depression of the immune system. Several reports have suggested that blood transfusion is a significant prognostic factor of outcomes in patients who underwent surgical resection of cancer [15,16,30,31]. The mechanisms involved in the adverse effects of red blood cell transfusion may be related to impaired immunity or enhanced inflammation, which may lead to tumor growth or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative blood loss and red blood cell transfusion have been reported as prognostic factors for other types of cancer, such as colorectal cancer, gastric cancer, hepatocellular carcinoma, ductal adenocarcinoma of the pancreas, and prostate cancer [11][12][13][14][15]. Although several studies have examined the impact of blood transfusion on prognosis [16,17], there are few studies demonstrating the association between the amount of intraoperative blood loss and the long-term outcome of patients with esophageal SCC following radical esophagectomy. The aim of this study was to determine retrospectively the independent prognostic factors, especially intraoperative factors such as blood loss, after curative resection of esophageal SCC.…”
Section: Introductionmentioning
confidence: 99%
“…Children with sickle-cell disease receive blood transfusions for a variety of reasons, such as severe malaria or sickle-cell crisis, but we are aware of no data suggesting that these conditions predispose children to HHV-8 infection. Still, heterologous blood transfusions have been reported to cause transient immunosuppression (35), and the higher prevalence of HHV-8 infection could conceivably be the result of heightened susceptibility in transfused children to infection from other sources. Nonetheless, in additional analyses stratified on number of blood transfusions, we did not obtain differing estimates of the risk for community-acquired infection (data not shown), suggesting that it is unlikely that transfusions serve merely as a marker for poor overall health and increased risk for community-acquired HHV-8 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Gharehbaghian et al demonstrated that use of autologous salvaged blood, instead of allogenic blood for transfusion, increased the proportion of NK cell precursors and IFNγ production post-surgery [ 81 ]. However, there was no difference in autologous vs. allogenic blood transfusion in NK cell cytotoxicity in Takemura’s study [ 82 ]. These results may be explained by the fact that blood transfusions themselves will result in immunosuppression.…”
Section: Surgical Stress Inflammation and Natural Killer Cell Dysmentioning
confidence: 99%